Additions to microfungi in China: Lentithecium yunnanensis sp. nov. - Lu, Wenhua; Dai, Dongqin; Lu, Li; Liu, Xiangfu; Wei, Xiaomei; Karunarathna, Samantha C.; Tibpromma, Saowaluck (Phytotaxa, 2022)
We describe a new fungal species of the genus Lentithecium, collected from dead culms of Artemisia sp. in Songhua Reservoir at Kunming, Yunnan Province, China. Multi-gene phylogenetic analyses of LSU, ITS, SSU, and tef1-α sequence data showed that our new fungal strain belongs to Lentithecium and is well separated from all other extant species of Lentithecium. Lentithecium yunnanensis sp. nov. is compared with all the extant species by morphological characteristics, culture characteristics, host, and location information and is the first report of Lentithecium from China on Artemisia. A comprehensive description, a color photo plate of microcharacteristics, and a phylogenetic tree to show the position of the new species are provided.